Lessons from the development of certified coffee suppliers promoted by an international trader in Veracruz, Mexico. - Alarcón Márquez, Maria Guadalupe; Santoyo Cortés, Vinicio Horacio; Altamirano Cárdenas, J. Reyes; Muñoz Rodríguez, Manrrubio (Agricultura, Sociedad y Desarrollo, 2024)
This study specifies the lessons from a development program for suppliers implemented for more than 10 years by an international coffee trader with small-scale producers in Mexico, to fulfill the voluntary sustainability standards (VSS) required by their most demanding markets. The information was obtained in the year 2021, through semi-structured surveys, with a random sample of coffee growers (n=54), interviews with technical advisers (n=8), and operating staff (n=6) of the company. The information was analyzed with a mixed approach, to characterize the program and estimate the differential costs and benefits for the company and its suppliers. Results show that the implementation of the program required investing to develop a more complex and costly grocer’s structure than purchases in the open market; however, the yields per hectare increased with the technical advice and better prices were attained from complying with the VSS. Thus, the trader stockpiled close to 2,400 additional tons of green coffee annually and managed to increase its profit in close to 7.4 million USD per year, with an estimated differential annual cost of 1.1 million USD. Likewise, coffee growers increased their income 1.7 times compared to a scenario without the program. The defining factor of these results is the presence of a “trailblazing company” with access to dynamic and solvent markets, which designed a mutual profit scheme with the small-scale producers and financed it with a vision in the medium term.